Tagore and the margins of the nation under colonialism - Mukhopadhyay, Amartya (Routledge, 2024)
"This book focuses on India’s anti-colonial politics which Rabindranath Tagore (1861–1941) brought into the mainstream of nationalist thinking. It browses through the entire corpus of Tagore’s writings in the genres of poetry, fiction, and essays, to glean both used and hitherto unused/un-translated writings that illumine Tagore’s gender consciousness and (proto)feminist thought and empathy, presenting it in a wholly new light. It teases out Tagore’s original views on India’s industrial-capitalist development and his views on the roles of applied scientists and engineers in it to highlight his critique of the nature of science teaching in colonial India. The volume also delineates Tagore’s Upanisadic ecologism that creatively evoked anticolonialism and patriotism.Lucid and topical, the book will be indispensable for students and researchers in the fields of comparative literature, history, political science, international relations, and sociology at all levels, and anybody interested in literary criticism and cultural studies."
Keywords: Tagore, Rabindranath -- 1861-1941; Antikolonialismus -- Motiv